If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2.5x+3=5.5x-6
We move all terms to the left:
2.5x+3-(5.5x-6)=0
We get rid of parentheses
2.5x-5.5x+6+3=0
We add all the numbers together, and all the variables
-3x+9=0
We move all terms containing x to the left, all other terms to the right
-3x=-9
x=-9/-3
x=+3
| -5x+34=-(7x+1) | | 2-5x=3(2x-4) | | 11x-5x+155=11x+85 | | 26x+3x^2=665 | | 33+(10x+37)=180 | | 10x+5x=20x-5x | | 26x+3^2=665 | | (x-3)(x+8)=x^2-7x-28 | | 9=–3(2t–7) | | 2-8s=42 | | 26x+3x2=665 | | 55-(9x-6)=-2 | | 3x=18x=5x-2 | | 8-4x=-2x+4 | | -18=9(u-98) | | 4(x+18)=6x+52 | | 12.4-1.5x=3.4 | | 8-4x=-2x4 | | 4y+272-3(323+y)=284 | | 13x+2-3x=4-2(2x+5) | | 3(10+2x)=-18 | | f/10+52=59 | | 8x+7=7x-2 | | 2/3x+9=3/4x-3 | | –4j=9−3j | | 3(x+9)=3x+16 | | 33.1=x-1.7 | | m/3+16=21 | | 149-u=193 | | 3.6=12g | | 4558/86=m | | x+2.5=2.5 |